2022
DOI: 10.1177/0271678x221077343
|View full text |Cite
|
Sign up to set email alerts
|

How expensive is the astrocyte?

Abstract: The energy cost of information processing is thought to be chiefly neuronal, with a minor fraction attributed to glial cells. However, there is compelling evidence that astrocytes capture synaptic K+ using their Na+/K+ ATPase, and not solely through Kir4.1 channels as was once thought. When this active buffering is taken into account, the cost of astrocytes rises by >200%. Gram-per-gram, astrocytes turn out to be as expensive as neurons. This conclusion is supported by 3D reconstruction of the neuropil show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 86 publications
4
23
0
Order By: Relevance
“…Interestingly, Lopez-Fabuel et al showed that decreased mitochondrial function and increased ROS production, promotes astrocyte survival while negatively influencing neuron viability [210]. This effect was further described by Weber and Barros, who discussed the “selfishness” of reactive astrocytes, observing that following injury or in response to disease, activated astrocytes will alter their metabolism and reduced their neuronal support functions to favour their own survival [211,212].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lopez-Fabuel et al showed that decreased mitochondrial function and increased ROS production, promotes astrocyte survival while negatively influencing neuron viability [210]. This effect was further described by Weber and Barros, who discussed the “selfishness” of reactive astrocytes, observing that following injury or in response to disease, activated astrocytes will alter their metabolism and reduced their neuronal support functions to favour their own survival [211,212].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astrocytes express the constitutively open Kir4.1 channels, which act as routes of K + entry and efflux (MacAulay, 2020 ), and maintain a hyperpolarized membrane potential. Spatial buffering of astrocytic K + is achieved where K + influx via Kir4.1 channels is counteracted by electrotonic repulsion of K + from distant astrocytes in the interconnected syncytium (Barros, 2022 ; Orkand et al, 1966 ). The combination of these transport mechanisms is computed as the most energy efficient means of buffering interstitial K + (Barros, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial buffering of astrocytic K + is achieved where K + influx via Kir4.1 channels is counteracted by electrotonic repulsion of K + from distant astrocytes in the interconnected syncytium (Barros, 2022 ; Orkand et al, 1966 ). The combination of these transport mechanisms is computed as the most energy efficient means of buffering interstitial K + (Barros, 2022 ). Astrocytes occupy 30% of the volume of the MON and contain 70% of the mitochondria (Perge et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that the levels of reduced c - and b -types cytochromes were lower in aged astrocytes reflecting the decreased amount of electrons in ETC which may limit the production of mitochondrial ATP and reactive oxygen species (ROS). Mitochondrial generation of ATP is critical for astrocytic homeostatic function, as ATP fuels Na + /K + ATPase responsible for K + buffering and maintenance of Na + gradients sustaining homeostatic transporters (Verkhratsky & Rose, 2020, Barros, 2022, Verkhratsky & Semyanov, 2022). ROS-signaling modulates brain metabolism and behavior (Vicente-Gutierrez et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%